Can Video Head Impulse Testing Be Used to Estimate the Involved Canal in Benign Paroxysmal Positional Vertigo? - Mustafa Uslu; Murat Eğrilmez; Murat Cem Miman (Journal of International Advanced Otology)
BACKGROUND: There may be confusion about which canal is involved in patients with benign paroxysmal positional vertigo (BPPV), especially with those that have subtle findings. The study aimed to determine if video head impulse testing may be used in such patients as a diagnostic tool. Symptom scoring and treatment efficiency in BPPV are essential parts of the process. Therefore, inventories like “Dizziness Handicap Inventory” may be useful in this regard.